The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1152/ajpheart.00953.2010
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary and systemic vasodilator responses to the soluble guanylyl cyclase activator, BAY 60–2770, are not dependent on endogenous nitric oxide or reduced heme

Abstract: 4-({(4-Carboxybutyl)[2-(5-fluoro-2-{[4'-(trifluoromethyl)biphenyl-4-yl]methoxy}phenyl)ethyl]amino}methyl)benzoic acid (BAY 60-2770) is a nitric oxide (NO)-independent activator of soluble guanylyl cyclase (sGC) that increases the catalytic activity of the heme-oxidized or heme-free form of the enzyme. In this study, responses to intravenous injections of the sGC activator BAY 60-2770 were investigated under baseline and elevated tone conditions induced by the thromboxane mimic U-46619 when NO synthesis was inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 25 publications
6
53
0
Order By: Relevance
“…However, the vasodilatory effects of BAY 41-8543 and BAY 60-2770 have been previously established to be mediated by the increase in cGMP in vascular smooth muscle cells. In separate studies, the in vitro efficacy of the sGC stimulator BAY 41-8543 and sGC activator BAY 60-2770 was demonstrated, which stimulates sGC directly to increase cGMP production and vasodilation (16,17,23,30,38). In addition, it was shown in other studies that this type of sGC stimulators (BAY 41-2272), indeed, directly stimulates sGC, hence enhancing renal cGMP production that results in an improved renal NO-cGMP signaling and limited progression in antiThy-1-induced chronic renal fibrosis (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the vasodilatory effects of BAY 41-8543 and BAY 60-2770 have been previously established to be mediated by the increase in cGMP in vascular smooth muscle cells. In separate studies, the in vitro efficacy of the sGC stimulator BAY 41-8543 and sGC activator BAY 60-2770 was demonstrated, which stimulates sGC directly to increase cGMP production and vasodilation (16,17,23,30,38). In addition, it was shown in other studies that this type of sGC stimulators (BAY 41-2272), indeed, directly stimulates sGC, hence enhancing renal cGMP production that results in an improved renal NO-cGMP signaling and limited progression in antiThy-1-induced chronic renal fibrosis (40).…”
Section: Discussionmentioning
confidence: 99%
“…sGC stimulators, such as BAY 41-2272 and Riociguat (BAY 63-2521), act directly on native, ferrous sGC that sensitizes sGC to low levels of bioavailable NO by stabilizing the nitrosyl-heme complex, maintaining the enzyme in its active configuration (4,34). In contrast, recently discovered sGC activators, such as BAY 60-2770 and BAY 58-2667 (cinaciguat), effectively activate sGC even when it is in an oxidized or heme-free state (16,23,29,34,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the modulation of NO/cGMP signaling is an important pharmacological target pathway for the prevention of cardiovascular diseases such as angina pectoris, hypertension, heart insufficiency, and atherosclerosis (7,57,62). The knowledge of the details regarding NO/cGMP signal transduction is essential for the understanding of the physiological and pathophysiological regulation and the modulation at diverse steps in this signaling pathway (Fig.…”
Section: Function Of No/cgmp/pkg Signaling Cascadementioning
confidence: 99%
“…137 In animal models of PH, sGC expression was similarly upregulated, and direct sGC activation improved hemodynamics and vascular remodeling. [137][138][139] A proof-of-concept study was conducted that included 19 adult patients with PH (either PAH or chronic thromboembolic PH) who received the new drug riociguat (BAY 63-251). 140,141 That study suggested that riociguat was safe and found that pulmonary hemodynamics and cardiac output improved in a dose-dependent fashion.…”
Section: Nitric Oxide-cgmp Cascade: Inhaled Nitric Oxidementioning
confidence: 99%